CLINICAL EFFECTIVENESS OF PERSONALIZED RISK ASSESSMENT AND INDIVIDUALIZED TREATMENT STRATEGIES IN UROLITHIASIS - Rahimov Doniyorjon Adhamjon o‘g‘li (Western European Studies, 2026)
Urolithiasis remains one of the most prevalent urological disorders worldwide, characterized by a high recurrence rate and significant socioeconomic burden. Conventional management strategies often fail to adequately account for individual metabolic, clinical, and lifestyle-related risk factors, limiting their long-term effectiveness. Objective: To evaluate the clinical effectiveness of personalized risk assessment and individualized treatment strategies in patients with urolithiasis. Methods: A comprehensive clinical and analytical assessment was conducted, incorporating demographic data, metabolic profiles, imaging findings, and stone composition analysis. Patients were stratified according to individual risk factors, and tailored therapeutic and preventive interventions were implemented. Clinical outcomes, recurrence rates, and treatment-related complications were systematically analyzed. Results: Personalized risk-based management demonstrated superior clinical outcomes, including a statistically significant reduction in stone recurrence and improvement in metabolic parameters, compared with conventional standardized approaches. Individualized treatment strategies were also associated with enhanced patient compliance and a lower incidence of procedure-related complications. Conclusion: Personalized risk assessment and individualized treatment strategies significantly improve clinical outcomes in urolithiasis and represent a promising direction for optimizing long-term disease management. Integration of individualized approaches into routine clinical practice may contribute to reducing recurrence rates and improving patient-centered care.
Keywords: urolithiasis; personalized medicine; risk stratification